Stacey's mistake - Martin, Ann M., 1955-; Crenshaw, Ellen T. (Baby-sitters Club (Graphix (Firm)), 2023)
When her friends from the Baby-sitters Club come for a visit in NYC, Stacey realizes they feel out of place in the big city and must find a way to keep the weekend from becoming a complete disaster.